Cardiac Threat Appraisal and Depression after First Myocardial Infarction - Vögele, Claus; Christ, Oliver; Spaderna, Heike (Frontiers in Psychology, 2012)
The present study investigated cardiac threat appraisal and its association with depression after first myocardial infarction (MI). A semi-structured interview allowing for DSM-IV-Axis I diagnoses was administered to 36 patients after first MI. Patients completed self-reports 5 to 15 days after the MI (time 1), 6 to 8 weeks later (time 2) and again 6 months later (time 3). Assessments at time 1 included indices of cardiac threat appraisal, locus of control, coping, and depression while at time 2 and time 3 only measures of depression were obtained. Cardiac threat appraisal was significantly correlated with depression at time 1, but was unrelated to depression scores at time 2 and time 3. Furthermore, there was a significant inverse association between cardiac threat appraisal and the subscales “search for affiliation” and "threat minimization" of the coping questionnaire. Additionally, “search for affiliation” correlated negatively with depression scores at time 1 and time 3, and "threat minimization" negatively with depression scores at time 1 and time 2. These results suggest a significant association between cardiac threat appraisal and depressive symptoms shortly after MI. Practical implications for treatment are discussed.